Efektivitas Media Infografis Berbahasa Arab dalam Meningkatkan Mahārah Qirāah Siswa Madrasah Tsanawiyah - Dini Hidayatul Nisak; Hasan Syaiful Rizal; Miftachul Taubah (STIQ Amuntai, 2026)
In Arabic language instruction at the Junior High School (MTs) level, students often encounter significant difficulties with maharah qiraah (reading skills), particularly in pronunciation accuracy and textual comprehension, due to a lack of innovative visual media. This study aims to evaluate the effectiveness of Arabic-language infographics as an instructional tool to enhance these reading competencies. A quantitative approach with a one-group pretest-posttest pre-experimental design was employed. The participants consisted of eighth-grade students at MTs Al-Islah Beji Pasuruan, selected through purposive sampling. Data were collected via oral reading tests, observations, and documentation. Analysis was performed using descriptive statistics, the Wilcoxon Signed-Rank Test for hypothesis testing, and N-Gain analysis to measure the magnitude of improvement. The findings revealed a substantial increase in students' reading proficiency, with the mean score rising from 41.48 in the pretest to 73.00 in the posttest. The Wilcoxon Signed-Rank Test yielded a significance value of 0.000 (p< 0.05). indicating a statistically significant difference following the intervention. Furthermore, a mean N-Gain score of 0.51 places the infographic media's effectiveness in the moderate category. The results demonstrate that Arabic infographics, supported by Dual Coding Theory and Cognitive Load Theory, effectively facilitate information processing by combining verbal and visual codes. Consequently, this media is recommended as an innovative alternative to optimise maharah qiraah instruction in Madrasahs.